Alloplastic Epidermal Skin Substitute in the Treatment of Burns - Aleksandra Barbachowska; Tomasz Korzeniowski; Agnieszka Surowiecka; Jerzy Strużyna (Life, 2023)
The goal of burn wound treatment is to ensure rapid epithelialization in superficial burns and the process of rebuilding the lost skin in deep burns. Topical treatment plays an important role. One of the innovations in the field of synthetic materials dedicated to the treatment of burns is epidermal skin substitutes. Since the introduction of Suprathel®, the alloplastic epidermal substitute, many research results have been published in which the authors investigated the properties and use of this substitute in the treatment of wounds of various origins, including burn wounds. Burn wounds cause both physical and psychological discomfort, which is why ensuring comfort during treatment is extremely important. Alloplastic epidermal substitute, due to its biodegradability, plasticity, no need to remove the dressing until healing, and the associated reduction in pain, is an alternative for treating burns, especially in children.